LEKSIKON BUDAYA DALAM HUKUM ADAT MASYARAKAT DAYAK KANTUK KECAMATAN PUTUSSIBAU UTARA KABUPATEN KAPUAS HULU - Vatria, Yuliana; Amir, Amriani; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstractâ€œDayak Kantukâ€ are one of many sub-ethnic that exist in a half of the Kapuas Hulu Regency, especially in District of Putussibau Utara, Palapulau village. The tribal laws is a such of norm that regulating the social life of people of Dayak. The tribal laws were made in indigenenous language which based on the tradition and the local wisdom. The culture of tribal laws are strongly bound with the tradition events, such as rites and customaries tradition. Custom rites is a part of tradition which had been inherited by the predecessors to the another generation in order to regulating the social life of the another generation. The laws is the tribal laws in spoken form and behaviour of social life. The tools are used in the research such as recorder, notebook, and documentation. Based on the data analysis, there are 58 data found of cultural lexicon of tribal laws based on the classification, 20 data of tribal laws lexicon, 14 data of customs lexicon, 18 data of curtural things, and 6 data of the actors lexicon.Keyword : Cultural Lexicon, Tribal Laws, Lingual Unit, Sense, Dayak Kantuk.